The novel null allele, HLA‐B*40:338N, was identified in a Chinese leukemia patient. (16th January 2018) - He, J.; Dong, L.‐N.; Wang, F.; Wang, W.; Zhu, F.‐M.
Abstract : HLA‐B*40:338N differs from HLA‐B*40:01:01 by a single nucleotide substitution at position 843C>A.